Evolution of structure and activity of char-supported iron catalysts prepared for steam reforming of bio-oil - Wang, Y.; Jiang, L.; Hu, S.; Su, S.; Zhou, Y.; Xiang, J.; Zhang, S.; Li, Chun-Zhu (Elsevier, 2017)
The aim of this study is to investigate the changes in iron phase, crystal size, surface area, and char structure/reactivity of the char-supported iron catalysts after them being used for bio-oil reforming. The catalysts were prepared under different conditions (varying in temperatures, gasification agents and iron concentrations) and then used to reform bio-oil under a fixed experimental condition at 800 °C. The results show that the catalysts prepared from the steam gasification of Fe-loaded coal were preferred in terms of catalytic performance. The X-ray diffraction analysis indicates that the iron phases in the fresh catalysts varied while the used catalysts nearly showed identical iron phase of magnetite (Fe3O4). The crystal iron particle in the catalysts would apparently increase after reforming when the initial iron phase was carbides (?-Fe and/or a-Fe). The char structure of the catalysts was significantly affected by the ‘volatile-char interactions’ during reforming process. And the catalysts’ surface area and reactivity in air were both reduced mainly due to the coke formation.